Psychogeography - Self, Will 1961- (Bloomsbury, 2007)
A volume of essays meditates on the complex relationship between psyche and place and evaluates the ways in which human-made geography has irrevocably shaped our emotions and behaviors while detaching people from the natural world.
Keywords: Self, Will - Travel; Self, Will -- Travel; Geography / Psychological aspects; Geographical perception; Environmental influence on humans; Geography - Psychological aspects; Human influence on nature; Geografie; Psychologie; Geography -- Psychological aspects; Human beings -- Effect of environment on; Nature -- Effect of human beings on; Umweltwahrnehmung; Fiktionale Darstellung